2013
DOI: 10.1080/20786204.2013.10874382
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a school-based nutrition and physical activity programme for Grade 4 learners in the Western Cape province

Abstract: Objective: This study aimed to evaluate the effectiveness of the Making the Difference programme (MTDP), an educationand activity-based intervention for Grade 4 learners at primary schools in the Western Cape.Design: This was a cross-sectional, post-intervention survey of an existing programme, using control schools as a comparator.Setting and subjects: The study involved Western Cape primary schools in the 2009 school year. Schools were randomly sampled from two regions. Four intervention (active in the MTDP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 23 publications
0
13
1
Order By: Relevance
“…Students who received the nutrition intervention scored significantly higher than the controls the second time both groups completed the Kuwait children nutrition knowledge questionnaire. The 11.0% score increase we found is higher than scores reported in similar studies (14,19) but lower than those of others (20,21). However, it is important to note that while we delivered a presentation-focused, interactive intervention, it was just one 60-minute session.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…Students who received the nutrition intervention scored significantly higher than the controls the second time both groups completed the Kuwait children nutrition knowledge questionnaire. The 11.0% score increase we found is higher than scores reported in similar studies (14,19) but lower than those of others (20,21). However, it is important to note that while we delivered a presentation-focused, interactive intervention, it was just one 60-minute session.…”
Section: Discussioncontrasting
confidence: 84%
“…The prevalence of childhood obesity in Kuwait is as high as 19.9% in children between 5 and 13 years of age (1) and has exceeded 30% in adolescents (2,3). Previous studies have found an association between nutritional knowledge and dietary intake, indicating that improving nutritional knowledge at an early age may help promote healthy eating patterns in children (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…20,29 Three primary school interventions apart from HK have been evaluated in South Africa. [30][31][32] One of these was undertaken by Jacobs et al 30 in Grade 4 learners in the Western Cape, where an existing and ongoing intervention was evaluated. Four intervention and five control schools were randomly selected from two school districts.…”
Section: Discussionmentioning
confidence: 99%
“…34 Although some school-based interventions have shown behavior change in similar age groups, 2,5,6,30,32,35 the low intensity of the intervention, the lack of significant changes in the school environment and the poor involvement of parents as described earlier 20 could have hindered children from making changes in their eating behavior. The improvement of nutrition knowledge is, however, an important achievement, and although nutrition knowledge on its own is not sufficient for behavior change, Worsley, 36 after a review of the literature, suggests that nutrition knowledge "may play a small but pivotal role in the adoption of healthier food habits.…”
mentioning
confidence: 99%
“…Less is known about school food environments in low- and middle-income countries, especially in sub-Saharan Africa. The bulk of evidence has been generated in South Africa (Claasen et al 2016 ; Faber et al 2014 ; Jacobs et al 2013 ; Meko et al 2015 ; Oosthuizen et al, 2011 ). For example, one study highlighted a number of issues in the school food environment such as the low content of fruits and vegetables in school meals, that about a quarter of the students did not eat breakfast, and the wide consumption of unhealthy food items bought in nearby tuck shops and by vendors located in the schools (Faber et al 2014 ).…”
Section: Introductionmentioning
confidence: 99%